The New International Financial Architecture and Africa - Nsouli, Saleh; Le Gall, Francoise (Washington, D.C. : International Monetary Fund, 2001)
The new international financial architecture can help African countries benefit from globalization, while minimizing the risks, and foster an environment conducive to increased domestic investment and higher sustained growth. This paper highlights the progress that African countries have made in several areas of the new architecture, but it also underscores the considerable way that these countries must go to meet the requirements of the new architecture.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet